AB0642 DESCRIPTION OF SAE1/2 ANTIBODY IN A DERMATOMYOSITIS COHORT. (June 2019) - Camins-Fàbregas, Jordi; Esteve-Cols, Clara; Casafont-Solé, Ivette; Martínez-Morillo, Melania; Aparicio-Espinar, Maria; Mateo, Lourdes; Riveros, Anne; Gifre, Laia; Sangüesa-Gomez, Clara; Prior-Español, Águeda; Nack, Annika; Brandy-Garcia, Anahy; et al.
Abstract : Background: Myositis specific antibodies have gained special importance in last years. Its knowledge has allowed stratifying patients in different clinical phenotypes, predicting with greater accuracy prognosis and establishing a clinical attitude to follow. SAE1/2 antibody (anti-small ubiquitin-like modifier activating enzyme) was first described in 2007 in patients with amyopathic dermatomyositis with cutaneous and digestive involvement. Its prevalence ranges from 8% in European cohorts to 3% in asians. Objectives: Describing myositis specific antibodies (MSA) in a cohort of inflammatory myopathies. To characterize the clinical phenotype of SAE1/2 antibody and to compare it with the rest of MSA. Methods: Patients diagnosed of dermatomyositis in a tertiary hospital from 1978-2018, according to the criteria of Bohan and Peter (1975) and according to Dalakas classification criteria (2015). Clinical and analytical data, including the immunological profile were collected, as well as the treatments received and the evolution of the disease. Results: Out of 46, 41 dermatomyositis had positive antinuclear antibodies (ANA). 55% percent had aNA titles≥640, being the fine speckled pattern the most frequent (43%) followed by coarse speckled and homogeneous (13.6% each). 72% had MSA, the most frequent being antiJo1 (27.3%) followed by MDA5 (18.2%) and SAE1/2 (15%). Up to 40% had two or more antibodies, being the association with antibodies Ro52 and Ro60, the most frequent. 5 patients presented positivity against SAE antibody. In comparison to the rest of MSA, 80% presented with cutaneous debut (p = 0.00), being the most frequent manifestations heliotrope erythema (p = 0.00), Gottron papules (p = 0.10) and skin rash (p = 0.00). 60% had pathological capillaroscopy compared to 15% (p = 0.00). Muscular balance was preserved in 60% of patients. Sixty percent had dysphagia vs 9% (p = 0.00). Two of them had lung involvement (alveolar hemorrhage and rapidly progressive pneumonitis). In comparison with SAE negative group, patients presented more pulmonary hypertension (44.5vs34 mmHg), without reaching significant differences. No significant differences were found between muscle enzyme levels' neither acute phase reactants. As complications, one patient presented a myocarditis with quickly rapidly progressive pneumonitis that required high doses of corticotherapy and another one alveolar hemorrhage, which was treated the same way. All patients required corticotherapy at doses of mg/kg, requiring two of them to be treated with DMARDs (methotrexate and dolquine) and one of them with immunoglobulins due to cutaneous involvement. Mortality rate was 40% due to rapidly progressive lung affectation and cardiorespiratory arrest. Conclusion: Higher prevalence of SAE1/2 antibody in our cohort may be explained due to the use of amplified myositis antibodies kit that specifically includes this antibody. These patients typically present with cutaneous involvement and dysphagia but also lung affectation as a complication. Studies with larger samples should be performed in order to know the prognosis of this antibody specificity. Disclosure of interests: None declared